2003
DOI: 10.1002/pi.1122
|View full text |Cite
|
Sign up to set email alerts
|

Grafting sulfobetaine monomer onto silicone surface to improve haemocompatibility

Abstract: Silicone rubber has been used as a biomaterial for more than two decades and displays good mechanical and optical properties, but its chemical nature, poor antithrombogenicity, as well as its hydrophobicity, prevents its use in many demanding biomedical applications. In order to provide modified silicone with enhanced haemocompatibility, surface modification techniques were used. Ozonization was used to introduce active peroxide groups onto the silicone film surface and, subsequently, graft polymerization of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…Among them, zwitterionic compounds such as phosphobetaine (i.e., phosphorylcholine) [59] and sulfobetaine derivatives [60][61][62][63] were found to be highly biocompatible. It was pointed out that the nonspecific adsorption of plasma protein onto the film of phosphobetaine copolymer was very small, and the adsorbed protein preserved the molecular structure [64].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, zwitterionic compounds such as phosphobetaine (i.e., phosphorylcholine) [59] and sulfobetaine derivatives [60][61][62][63] were found to be highly biocompatible. It was pointed out that the nonspecific adsorption of plasma protein onto the film of phosphobetaine copolymer was very small, and the adsorbed protein preserved the molecular structure [64].…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of surfaces with excellent biocompatibility, including poly(ethylene glycol)-grafted surfaces, [2][3][4] phase-separated microdomain surfaces, [5,6] bioactive molecule-incorporated surfaces, [7,8] and surfaces of zwitterionic compounds, [9][10][11][12][13][14] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Zwitterionic compounds such as phosphobetaine (i.e., phosphorylcholine) and sulfobetaine polymers are now widely used as biomaterials and for surface treatment to afford biocompatibility. [9][10][11][12][13][14] For instance, various phosphobetaine polymers containing 2-methacryloyloxyethyl phosphorylcholine (MPC) residues are used for non-thrombogenic coatings on Biodiv Ysio TM coronary stents and Proclear 1 contact lenses to reduce protein adsorption. Such a resistance against biofouling has been pointed out to be crucial for the appearance of biocompatibility of the polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…[38,39] Polymer films composed of butyl methacrylate (BMA) and a zwitterionic monomer such as 2-methacryloyloxyethyl phosphorylcholine (MPC), 3-sulfo-N,N-dimethyl-N-(3 0 -methacrylamidopropyl)propanaminium inner salt (SPB) and 1-carboxy-N,N-dimethyl-N-(2 0 -methacryloyloxyethyl)methanaminium inner salt (CMB) were found to be highly biocompatible. [40][41][42][43][44] The solution behavior of zwitterionic polymers has received much attention due to unique properties to typical polyelectrolytes. [45][46][47] We have observed the structure of water in the vicinity of many kinds of zwitterionic polymers by Raman and attenuated total reflection (ATR) infrared spectroscopy, and found that the hydrogen-bonded network structure of the vicinal water is not largely disturbed.…”
Section: Introductionmentioning
confidence: 99%